Indigenous and non‐Indigenous parents separated from their children and experiencing homelessness and mental illness in Canada. Issue 8 (8th October 2020) - Caplan, Rachel; Nelson, Geoffrey; Distasio, Jino; Isaak, Corinne; Edel, Betty; Piat, Myra; Macnaughton, Eric; Kirst, Maritt; Patterson, Michelle; Aubry, Tim; Mulligan, Susan; Goering, Paula
Abstract: The purpose of this study is to examine the parent–child experiences of Indigenous and non‐Indigenous mothers and fathers experiencing homelessness, mental illness, and separation from their children. A qualitative thematic analysis of baseline and 18‐month follow‐up narrative interviews was used to compare 12 mothers ( n = 8 Indigenous and n = 4 nonindigenous) with 24 fathers ( n = 13 Indigenous and n = 11 non‐Indigenous). First, it was found that children are more central in the lives of mothers than fathers. Second, Indigenous parents' narratives were characterized by interpersonal and systemic violence, racism and trauma, and cultural disconnection, but also more cultural healing resources. Third, an intersectional analysis showed that children were peripheral in the lives of non‐Indigenous fathers, and most central to the identities of Indigenous mothers. Gender identity, Indigenous, and intersectional theories are used to interpret the findings. Implications for future theory, research, and culturally relevant intervention are discussed.